Navigating Contradictions for Organizational Agility: A Systematic Literature Review on the Paradox Mindset in the Workplace - Nguyen, Cuong; Nguyen, Duc (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2025)
The objective of this study is to synthesize the extant literature on paradox mindset, delineating its conceptual boundaries, antecedents, mediators, moderators, and outcomes in organizational settings. Drawing on 95 peer-reviewed journal articles published between 2008 and 2024, and employing a PRISMA-aligned Systematic Literature Review (SLR) methodology, the review categorizes theoretical and empirical contributions across levels of analysis. Findings indicate that paradox mindset research is primarily grounded in organizational paradox theory, with extensions into leadership, creativity, employee resilience, and ambidexterity. The paradox mindset is associated with beneficial organizational outcomes—including innovation and promotive voice—through mechanisms such as cognitive reappraisal, perspective-taking, and intrinsic motivation. These effects are shaped by contextual moderators, including paradoxical leadership and organizational culture. The study concludes that the paradox mindset serves as an integrative cognitive capability that fosters agility, adaptability, and sustainable performance.